(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
The legislator empowers legally the tax administration a number of guarantees for instance the right of control. The tax administration may lead deep or corrected investigations. The investigation phase starts after the expiry of taxation period gruanted by the administration. The subject to tax has many rights such us, the limitation of the investigation , the presence and finally have a consultant . Key words- taxi subject, tax administration, accointintance investigation , deep investigation, right to have a consultant.